Analysis of the Effect of Internet Social Networks on Societal Development - Ikenna, Oluigbo; Chinyere, Okpara; Ikenna, Ajere (IJRDO - Journal of Applied Management Science, 2015)
Social Network is an Internet application in the field of Information Technology to study and assess relationships between individuals, groups, organizations, or even entire societies. Social media offers a range of new possibilities for individuals and organisations working for social good. The aim of this research is to identify a number of social networks in existence, and evaluate the individual and collective effects (both positive and negative effects) these social networks have on societal growth and development. Five social networks were identified; Facebook, Twitter, Bebo, Hi5 and MySpace, which forms the independent variables. The study used a population size of 100 respondents, with a sample size of 80 respondents. Data were collected and analyzed through quantitative and qualitative methods and the use of regression analysis was used in testing of the hypothesis at a 0.05 significant level. From the researchers’ findings, the respondents agreed that there is a significant effect of individual social network and the collective social networks on societal development. Therefore, social networks can be an effective tool for individual and organisation’s growth, as well as having a sizeable impact on the development of a society.